Nitrogen Fixation in Preserved, Reforested, Naturally Regenerated and Impaired Mangroves as an Indicator of Functional Restoration in Mangroves in an Arid Region of Mexico - Vovides, A.G.; Bashan, Y.; López-Portillo, J.A.; Guevara, R.
Although several damaged mangrove ecosystems have been restored worldwide, so far, it has not been established whether a restored mangrove system regains all the functional properties of preserved mangroves. This study measured nitrogen fixation as an indicator of whether disturbed mangroves that were reforested or naturally regenerated fully recovered from this disturbance at a functional level. Rates of nitrogen fixation were measured for one year in impaired, preserved, reforested, and naturally regenerated mangroves dominated by the black mangrove (Avicennia germinans). There was no significant difference in rates of nitrogen fixation among preserved and adjacent reforested and naturally regenerated mangroves, but a significant reduction occurred in an impaired mangrove. Nitrogen fixation was mainly controlled by pH, salinity, and temperature. The highest rates of nitrogen fixation occurred in summer at pH values less than 6.4, whereas the impaired mangrove had higher pH and salinity and had very low nitrogen fixation activity. These results suggest that nitrogen fixation can be used as an ecological indicator of the success of reforestation and as a sensitive measure of perturbations in mangroves.
Keywords: AVICENNIA GERMINANS; FUNCTION RESTORATION; NITROGEN FIXATION; REFORESTATION